Corticosteroids for Septic Shock: Another Chapter in the Saga. (April 2020) - Yerke, Jason; Strnad, Kyle; Bauer, Seth R.
The use of corticosteroids in the management of septic shock has been a highly debated topic for quite some time. Corticosteroids have the ability to combat hyperinflammatory and exaggerated vasodilatory responses, as well as to sensitize adrenergic receptors to decrease the duration of shock. While helpful clinically, this has not translated to consistent mortality benefits. Conflicting results from 2 landmark trials published in 2002 and 2008 have led to varying clinical practices, and a clearly defined role of corticosteroids in septic shock is lacking. A decade later, an influx of new data derived from 2 more large trials continues to echo diverging viewpoints regarding patient mortality. In combination with fluctuating study designs (eg, adjunctive therapies and shock management) and patient populations (eg, illness severity), generalized conclusions are still difficult to draw. Despite these challenges, this review critically analyzes recently published data in the context of historical debate to provide an updated comment on the role of corticosteroids in septic shock. In summary, hydrocortisone therapy is likely to demonstrate maximal benefit when initiated on patients with septic shock and organ failure refractory to vasopressor therapy and should be used judiciously in other settings as it comes without a demonstrated benefit in mortality and increased potential for adverse effects.